Implementing Knowledge Management in Private Higher Education Institutions: The Role of Information Technology in Managing Academic Data to Foster Educational Innovation: Implementasi Manajemen Pengetahuan di Perguruan Tinggi Swasta: Peran Teknologi Informasi dalam Pengelolaan Data Akademik untuk Meningkatkan Inovasi Pembelajaran - Eriza RikaSari, Fajar; Riana, Dewi; Indrawani Turan, Septi; Nugroho Hidayanto, Dwi (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
This study aims to analyze the implementation of knowledge management systems supported by information technology (IT) in private universities (PTS) in Samarinda. The focus is on the role of IT in managing academic data, fostering learning innovation, and enhancing operational efficiency. The research adopts a mixed-method approach, combining quantitative surveys of students, lecturers, and administrative staff with in-depth interviews with institutional leaders and educators. Survey results reveal that most PTS are still in the early stages of adopting IT-based knowledge management systems, with many relying on manual methods or non-integrated systems. The primary challenges identified include limited technological infrastructure, insufficient digital literacy, and inadequate budget allocation. However, institutions that have implemented web-based IT systems reported significant improvements in academic data management efficiency, such as a 50% reduction in administrative processing time, along with increased user satisfaction. The key recommendations of this study include investing in IT infrastructure, such as upgrading server capacity and internet networks, providing comprehensive training for all users, and strengthening partnerships with technology service providers. These strategic measures are expected to accelerate digital transformation, improve the quality of academic services, and create a more innovative, adaptive, and competitive learning environment. This study highlights the crucial role of IT in enhancing the competitiveness of higher education institutions in the global digital era.